Aquaporins1 and 3 in the tissues of Paramisgurnus dabryanus and their expression profiles in response to ammonia and drought - Huang, Mei; Zhang, Lin-Jiang; Wu, Meng-Xiao; Peng, Gao-Feng; Zhang, Yun-Long (Frontiers in Marine Science, 2022)
Aquaporins (Aqp)1 and Aqp3 are the representatives of two types of aquaporins (classical aquaporin and aquaglyceroporin) and have been proven to potentially facilitate ammonia detoxification in air-breathing fishes. Paramisgurnus dabryanus is one of East Asia’s most important commercially farmed species and can breathe air directly through its hindgut. Besides, excellent ammonia tolerance was reported in this species. However, the mechanisms of its tolerance of high ammonia are still unclear. To explore the physiological roles of Aqp1 and Aqp3 in Paramisgurnus dabryanus, we detected the expression pattern of these two Aqps in several tissues and their transcriptional changes in response to different levels (30, and 70 mmol L-1 NH4Cl) and periods (0, 12, 48, and 96 h) of ammonia exposure and different periods (0, 12, 48, and 96 h) of drought stress. The aqp1 mRNA showed a high abundance in the brain and the osmoregulatory tissues, such as the intestine and kidney. While aqp3 was mainly expressed in the epithelium of skin and gills that were directly exposed to the environment. The expression level of aqp3 in gills was more responsive than aqp1 to ammonia challenges, although both of them were up-regulated. Considering the wide difference between aqp1 and aqp3 in the skin, aqp3 increased significantly after 12 h of air exposure. The changes of the two aqps in the intestine of P. dabryanus were relatively stable after ammonia stress. After drought stress, intestinal aqp1 increased significantly, while aqp3 decreased. Combined with the effects of tissue location and environmental stress on Aqps, it was suggested that Aqp1 was mainly involved in osmotic regulation, providing water as raw material for body metabolism. Accordingly, our results suggest that Aqp3 has the positive function of assisting ammonia transportation and epidermal moisturizing.